2016
DOI: 10.1111/nyas.13168
|View full text |Cite
|
Sign up to set email alerts
|

Normal and abnormal physiology, pharmacology, and anatomy of the gastroesophageal junction high‐pressure zone

Abstract: The high-pressure zone of the gastroesophageal junction acts as a multifunctional valve that comprises different groups of smooth muscles located in the distal esophagus and the proximal stomach, in addition to the extrinsic crural diaphragm, composed of skeletal muscle. In this review article, we evaluate the current literature with respect to human subjects, discussing the anatomic locations and physiologic and pharmacologic processes controlling these muscles. These muscles work individually and as a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…79,81,89,90 Currently it is believed that the LES consists of several different components, to include the gastric clasp muscle (located at the lesser curvature of the stomach), gastric sling muscle (located at the cardia), longitudinal outer smooth muscle, and the crural diaphragm that serves as an antireflux barrier. 81,89,90 The phrenoesophageal ligament attaches the lower esophagus to the diaphragm and brings the distal esophagus back to neutral position following peristalsis. 81 Proper functions of these structures play an important role in swallowing and reflux/antireflux mechanisms.…”
Section: The Gej and The Lesmentioning
confidence: 99%
“…79,81,89,90 Currently it is believed that the LES consists of several different components, to include the gastric clasp muscle (located at the lesser curvature of the stomach), gastric sling muscle (located at the cardia), longitudinal outer smooth muscle, and the crural diaphragm that serves as an antireflux barrier. 81,89,90 The phrenoesophageal ligament attaches the lower esophagus to the diaphragm and brings the distal esophagus back to neutral position following peristalsis. 81 Proper functions of these structures play an important role in swallowing and reflux/antireflux mechanisms.…”
Section: The Gej and The Lesmentioning
confidence: 99%
“…These units and their contribution to the physiology have been the source of some debate over the past few decades, but recent advances in imaging modalities and close examination of clinical correlations are bringing the field closer to a unified understanding. It has been proposed that the sum of these units be referred to as the gastro‐esophageal junction high‐pressure zone (GEJHPZ) (Miller, Vegesna, Ruggieri, & Braverman, 2016). The proposed components are the lower esophageal circular muscle sphincter (LECS), the upper gastric sphincter (UGS), the crural diaphragm with its phrenoesophageal ligament, and the gastroesophageal flap valve (GEFV) (Miller et al, 2016; Xie et al, 2017).…”
Section: Reflux Barrier Anatomymentioning
confidence: 99%
“…Some anatomical studies showed thickening of the circular muscle in the distal esophagus (Apaydin, Uz, Elhan, Loukas, & Tubbs, 2008). Furthermore, a manometric study selectively paralyzing skeletal and smooth muscle components of the GEJHPZ showed a distinct pressure peak proximal to the peak created by the UGS in the absence of diaphragm contraction (Brasseur et al, 2007; Miller et al, 2016). This indicates that there is a ring of tonically contracted smooth muscle located within the region of the phrenoesophageal ligament that is distinct from any gastric muscle fibers.…”
Section: Reflux Barrier Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a quite old finding from animal [9] and human [10] studies that the crura of the diaphragm play an important role in closure of the lower esophagus [11]. Especially a dissociation of the lower esophageal sphincter from the position of the diaphragmatic crura as seen in hiatal hernia seems to be an important mechanism for gastroesophageal reflux [12,13].…”
Section: Introductionmentioning
confidence: 99%